PENGARUH GAYA KEPEMIMPINAN GUBERNUR RIDWAN KAMIL TERHADAP KUALITAS PELAYANAN DI JAWA BARAT - Muhamad Nurfauzan; Idil Akbar; Rudiana Rudiana (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This study aims to describe the significance of the influence of the leadership style of the West Java Governor for the 2018-2023 period on the quality of public services in the West Java Provincial Government in 2023. West Java Province is the most populous province in Indonesia, so it is a challenge for the West Java provincial government to provide excellent public services for all its citizens. The influence of a leader who can make efforts to improve the quality of public services is needed. The method used is quantitative. The data collection technique was carried out by distributing questionnaires to 100 respondents. In this research, a series of statistical data analysis was carried out to test the proposed hypothesis, the results of which were presented descriptively. The results obtained were 14.190>1.661 with a significance value of <0.001 and a correlation of 0.820 or in a very strong category. Where the leadership style of the West Java Governor for the 2018-2023 period has an effect of 66.9% on the quality of public services in the West Java Provincial Government in 2023.